Inhibition of acute inflammation in the periphery by central action of salicylates. - Catania, A (1991)
Understanding of the antiinflammatory actions of nonsteroidal drugs is incomplete, but these actions are believed to occur in the periphery, without any contribution from the central nervous system. Recent research on the antipyretic antiinflammatory neuropeptide alpha-melanocyte-stimulating hormone indicates that it can act centrally to inhibit peripheral inflammation; this raises the possibility that other agents, such as nonsteroidal antiinflammatory drugs, may have similar activity. In the present research both lysine acetylsalicylate and sodium salicylate inhibited edema, induced in the mouse ear by topical application of picryl chloride, when injected into the lateral cerebral ventricle. This inhibitory activity on a measure of acute inflammation was not due to escape of the drugs into the periphery, because systemic injection of doses that were effective centrally did not affect inflammation. In contrast, central administration of a dose of indomethacin that was antiinflammatory when given intraperitoneally did not inhibit peripheral inflammation. Thus indomethacin apparently lacks the central antiinflammatory action of the salicylates. This observation, plus our inability to demonstrate either an antiinflammatory effect of intracerebroventricular dexamethasone, a prostaglandin inhibitor, or a pro-inflammatory influence of prostaglandin E2, suggests that prostaglandins are not important to central modulation of inflammation. The results indicate that, in addition to having central influences on fever and pain, salicylates can act within the brain to inhibit acute inflammation in the periphery.